PENGARUH TIPE PENENTUAN TUJUAN (GOAL SETTING) TERHADAP PERFORMANSI BAHASA INGGRIS SISWA: DENGAN EFIKASI DIRI DAN KEMAMPUAN AWAL BAHASA INGGRIS SEBAGAI KOVARIABEL - Ghozali Rusyid Affandi; Thomas Dicky Hastjarjo (University of Merdeka Malang, 2010)
Abstract This study aimed to assess the effect of goal setting types (performance goals, learning goals and do your best goals) on the students performance of English language by making self-efficacy and students' prior ability as co-variables. The design of this study used a quasi-experimental method and consist of three groups in which each would receive different treatment (learning goals, performance goals and do your best goal). Students performance of English language as measured by performance tests using the English language, self-efficacy was measured using self-efficacy scale and the prior ability of students is obtained from the result of English lesson in last assignment in class XI of 2nd semester. Subjects in this study amounted to 91 students a class XII of senior high school xxx in Yogyakarta. Analysis of the data used analysis of covariance (Ancova) and comparison analysis used analysis of variance (Anova). The result of data analysis by using Ancova with one tail shows that the hypothesis is proven, with F = 2,846 and p = 0.032 (p 0,05). The result indicates that there is a performance difference of the English language between types of goal-setting. LSD result indicates that differences in the performance of English language only occur between a given learning goals with performance goals with MD = 1,974 and p = 0,019 (p 0,05). Adjusted R Squared by co-variable (self-efficacy and prior ability) showed a higher result (24.3%) than those that were not using co-variable (7.3%). This is due to influence from both co-variables, i.e. self-efficacy (F = 4,124 p = 0,045 (p 0,05)) and the prior ability of students (F = 10.350 and p = 0.002 (p 0,01)), on the students performance of English language. These results indicate that in the application of goal settings techniques on the performance of the English language, it is needed to involve self efficacy and the students' prior ability in order to enhancing better results. Key words: Types of goal setting, learning goals, performance goals, do your best goals, self-efficacy and students' prior ability.